Tantangan Implementasi Nilai-Nilai Profil Pelajar Pancasila dalam Pembelajaran Bahasa Indonesia pada Kurikulum Merdeka Belajar - Israwati Amir; Nursalam Nursalam; Irvan Mustafa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The purpose of this study is to describe the implementation of the Pancasila student values ​​profile. This research is a qualitative research. The data sources of this research are teachers and books. The data collection techniques of this research are observation and documentation. The results of this study found that the lack of interest in students' reading is one of the challenges of the profile of Pancasila students' values ​​in learning Indonesian. Then, do not pay attention to the parents of students and do not understand understanding as a guardian of students. Furthermore, Indonesian language learning achievements are focused on developing language competencies, namely listening, speaking, reading, and writing.